2022
DOI: 10.1080/23802359.2022.2055501
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Atriplex gmelinii C. A. Mey. ex Bong. (Amaranthaceae)

Abstract: Atriplex gmelinii C. A. Mey. Ex Bong._1838 is an annual halophytic herb found in East Asia and North America. The chloroplast genome of A. gmelinii was successfully sequenced. The assembled genome (151,852 bp; GC ratio, 37.3%) is composed of four subregions, with the large single copy (LSC; 83,872 bp; 35.4%) and small single copy (SSC; 17,812 bp; 30.9%) regions separated by two regions of inverted repeat regions (25,084 bp; 42.8%). A total of 130 genes were predicted with 85 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…After obtaining the first draft of the chloroplast genome sequences, gaps were filled with GapCloser v1.12 (Zhao et al, 2011) and all bases from the assembled sequences were confirmed by checking each base in the alignment (tview mode in SAMtools v1.9) (Li et al, 2009) against the assembled chloroplast genome generated with BWA v0.7.17 (Li, 2013). All of these processes were conducted under the environment of Genome Information System (GeIS; http://geis.infoboss.co.kr/), which has been utilized in a range of studies (Kim et al, 2021b(Kim et al, , 2021c, including work on plant organelle genomes (Suh et al, 2021;Park et al, 2022aPark et al, , 2022cYoo et al, 2023).…”
Section: Genome Sequencing and De Novo Assembly Of The Two Agrimonia ...mentioning
confidence: 99%
“…After obtaining the first draft of the chloroplast genome sequences, gaps were filled with GapCloser v1.12 (Zhao et al, 2011) and all bases from the assembled sequences were confirmed by checking each base in the alignment (tview mode in SAMtools v1.9) (Li et al, 2009) against the assembled chloroplast genome generated with BWA v0.7.17 (Li, 2013). All of these processes were conducted under the environment of Genome Information System (GeIS; http://geis.infoboss.co.kr/), which has been utilized in a range of studies (Kim et al, 2021b(Kim et al, , 2021c, including work on plant organelle genomes (Suh et al, 2021;Park et al, 2022aPark et al, , 2022cYoo et al, 2023).…”
Section: Genome Sequencing and De Novo Assembly Of The Two Agrimonia ...mentioning
confidence: 99%